Financial Rights of Journalists in Media Institutions (Raparin Journal of Humanities (RJH), 2021)
In order to achieve the objectives of the study, this descriptive research is divided into three main chapters; the first chapter introduces the research methodology, while the second chapter addresses the theoretical part with the major focus on the rights and responsibilities of journalists within the frame of law. Finally, the third chapter is devoted to present the practical part in addition to statistical analysis to the collected data taken from the population of the study which embraces neighborhoods and suburbs of Sulaimaniyah.            For the primary data collection, this descriptive research relied on distributing one hundred and fifty questionnaires shared among one hundred and fifty media professionals who work for Gali Kurdistan Media Agency and NRT Channels. Then, the collected data went through an adequate and comprehensive analysis by means of SPSS. At the end of this research, many results were pointed out, above all, the study found that the law in force fails to provide and secure the rights of journalists in Kurdistan Region.